Terror and Joy : The Films of Dusan Makavejev - Mortimer, Lorraine (Book collections on Project MUSE., 2009)
Dušan Makavejev is a filmmaker, teacher, and intellectual whose films intersect with major historical and political upheavals in Eastern Europe-World War II, the unification and breakup of Yugoslavia, and the fall of communism. Subversive and moving, his films remain touchstones for transcultural and political cinema. Matching the intensity of the films, Lorraine Mortimer takes a radically interdisciplinary approach in this first book-length critical analysis of Makavejev's work.